Materials and technologies in construction with reference to energy efficiency and sustainable development - Kamal, Mohammad Arif (Key engineering materials, 2016)
This special topical volume on is aimed to cover the recent advancements and trends in the area of building materials with reference to energy efficiency and sustainable development. The volume will be of special interest to environmentally-minded producers of building materials and to engineers, architects and building professionals, but it may also be of use to readers and researchers who are interested in building construction but who lack specialist technical knowledge.